2022
DOI: 10.1002/anie.202201169
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Stacking on Graphene

Abstract: The sequential vertical polyfunctionalization of 2D addend‐patterned graphene is still elusive. Here, we report a practical realization of this goal via a “molecular building blocks” approach, which is based on a combination of a lithography‐assisted reductive functionalization approach and a post‐functionalization step to sequentially and controllably link the molecular building blocks ethylpyridine, cis‐dichlorobis(2,2′‐bipyridyl)ruthenium, and triphenylphosphine (4‐methylbenzenethiol, respectively) on selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…In the corresponding AFM image (Figure 5) these parallel ribbons can nicely be visualized, corroborating the structuring and morphological alteration of the graphene surface. To our knowledge, such an extending of pronounced topography changes has never been observed in previous 2D‐patterned graphene samples carrying only one layer of addends [15–18] . Moreover, the cross‐sectional height profile elucidates a 12 nm difference in height between the pattered regions (ribbons) and the unpatterned areas, in good agreement with the results obtained from STEM‐EDS.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In the corresponding AFM image (Figure 5) these parallel ribbons can nicely be visualized, corroborating the structuring and morphological alteration of the graphene surface. To our knowledge, such an extending of pronounced topography changes has never been observed in previous 2D‐patterned graphene samples carrying only one layer of addends [15–18] . Moreover, the cross‐sectional height profile elucidates a 12 nm difference in height between the pattered regions (ribbons) and the unpatterned areas, in good agreement with the results obtained from STEM‐EDS.…”
Section: Resultssupporting
confidence: 89%
“…Breaking this bottleneck was realized by using a novel “molecular building block” route that we developed for the 2D‐patterning of graphene towards sophisticated architectures in which three distinct building blocks were vertically grown on a defined graphene lattice. The process is implemented by an initial covalent 2D‐patterning of the graphene lattice, followed by a two‐step post‐functionalization [18] . Despite its significance, this approach suffers from an inherent drawback, namely, that the patterned multiple functionalities cannot stay fully vertical and consequently adopt varying conformations, whereby the resulting architectures are less controlled and more disordered, rendering the targeted 3D‐patterned architecture geometrically unstable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the covalent bond formation in graphene mediated by radicals has been widely reported in the literature. 58–61 For this, we applied a recent laser-induced functionalization protocol developed by Hirsch and co-workers 62–69 using dibenzoyl peroxide (DBPO) to graft phenyl groups on the surface of graphene according to Fig. 3a.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas chemical modifications offer great promise for expanding the functionalities and potential applications of graphene, the chemical inertness of the basal plane limits the available reaction approaches. Spatial patterning of chemical modifications presents yet another level of challenge. Radical reactions provide key routes to graphene functionalization. ,,, Our recent work has shown that in aqueous solutions, free radicals electrochemically generated at the graphene surface permit efficient reactions. In particular, in aqueous NaN 3 solutions, electrochemically generated azidyl radicals (N 3 ·) effectively azidate monolayer graphene, hence providing a versatile product that enables chemically defined derivations through click chemistry and subsequent bioconjugation …”
Section: Introductionmentioning
confidence: 99%